Mathletics software and student attainment in grade 4- a cultural historical analysis - Hardman, Joanne; Raudzingana, Mashudu (Advances in Social Sciences Research Journal, 2021)
Mathletics is a networked mathematics software package that affords students the opportunity to solve problems. This software is extremely popular in the developed world (Day, 2013) and is gaining popularity in the developing world as a tool that can potentially impact students’ mathematics attainment. 25 years after democracy South Africa continues to lag behind the rest of the world in mathematics and science attainment (Isdale, Reddy, Juan & Arends, 2017). The use of computer-based software packages to meet the needs of developing students’ understanding of mathematics is, therefore, of interest in our context. However, research is clear that it is not technology itself that can lead to learning but rather, how this technology is used; that is, the pedagogical practices underpinning the use of technology serves to develop understanding. This study sought to investigate Mathletics ability to impact positively on student attainment as well as their understanding. Findings indicated that Mathletics software does not build mediation into its programme and, therefore, does not develop conceptual understanding. In relation to student’s attainment, findings indicated that children did not perform better after using Mathletics on a summative test of calculation problems, pointing to the importance of pedagogical underpinnings when using technology.